Tracing the Trends of General Construction and Demolition Waste Research Using LDA Modeling Combined With Topic Intensity - Wu, Zezhou; Xie, Peiying; Zhang, Jinming; Zhan, Baojian; He, Qiufeng (Frontiers in Public Health, 2022)
The research on construction and demolition waste (CDW) has attracted more and more attention with the ever-increasing CDW pollution caused by large-scale infrastructure construction over time. This study utilized latent Dirichlet allocation (LDA) combined with topic intensity to discover research hot topics and development trends in the research areas of CDW to identify the status of CDW research. Firstly, the LDA was used for topic modeling to extract the existing topics from the text data. Then, the topic intensity was calculated for the extracted topics, and the numerical values of the topic intensity represented the popularity of the topics. In this study, four topics were extracted from 1849 relevant articles through the LDA modeling and topic intensity calculation. Results showed that the topic of “construction and demolition waste management” had an upward trend. Topics such as “Recycled aggregate”, “Environmental impact”, and “Study of CDW on soil” all showed a downward trend. Methods of this study can dig deeper into the topics of the CDW research domain and help scholars to engage in this field to understand the prevalence and evolution trends of these topics.